The Effect of Team Pair Solo Technique on Students’ Reading Comprehension of Narrative Text at Grade IX of SMPN 14 Pekanbaru - Meliza Aprela Yati; Hermawati Syarif; Zul Amri (English Language Teaching and Research, 2018)
Technique in teaching is one of the factors to develop students’ reading achievement. Therefore, teachers have to find the appropriate technique to encourage students become interested on reading activity and achieve the teaching learning reading’s goal. Team Pair Solo is one of the teaching techniques. This technique helps the students to comprehend the text through interactive way and discussing. Each step of this technique invites the students to participate and more active during learning activities. This research was quasi experimental research that aims at testing whether Team Pair Solo Technique produces better reading comprehension of narrative text compared to Lecture Technique. The population of this research was grade IX students of SMPN 14 Pekanbaru in 2017/2018 academic year consisting of 7 classes. The sample was selected by using cluster random sampling technique. They were IX.4 as experimental class and IX.2 as control class. Both classes consist of 27 students. The data were obtained from score of reading test. Research data were analyzed by using t-test. The result shows that Team Pair Solo Technique produces better reading comprehension of narrative text compared to Lecture technique at grade IX students of SMPN 14 Pekanbaru.Keywords- reading comprehension, team pair solo